Investigating information revelation on Facebook towards information privacy threats based on user characteristics / Sitinor Megawati Saurani - Saurani, Sitinor Megawati (2015)
worldwide and become a trending for people to get communicated nowadays. These network applications offers an attractive means of communication and interaction among online networks users but it also raise a concern on information privacy aspect. Most of these online applications require some personal information once we registered and joined this networks. These information are being widely viewed by public once we have registered and started the online communication with others. With all these information available online, there were chances of others to use this information. Some may be for good reason but some may be for the otherwise. Information privacy threats such as identity theft, phishing, digital tracing happens every day. This research shall looked into the online user characteristics which focus on Facebook user that expose to this threats. This research will analyse how information revelation could trigger the online information privacy threats using the respondents from undergraduate student and postgraduate student. Finding shows that social networks user do aware about information sharing and concern about information sharing. When information gets more personal, there will be likely less information being shared. Findings also shows that student who had experience in working, spends more time on social networks compare to those who do not have working experience or student who just started their college life. The present study has examine the personal information that university students disclose in their Facebook profile. Thus this research is important to understand how students in UiTM reveal their information and how to protect themselves from information privacy threats.